KEMUNGKINAN PENGGUNAAN LATEX UNTUK STABILISASI BADAN JALAN HUTAN - Rahardjo S Suparto; S Sutopo (Jurnal Penelitian Hasil Hutan, 1986)
Among  the many known  stabilized methods  and materials that can be applied to improve forest  road stability,  latex is thought  of as one such material  that deserves trying.   This experiment  is to asses the possibility  of  using latex as a stabilizing  agent,The fol/owing   conclusions  are in order: Latex  can be used as stabilizing  agent for  clayey soils as subgrade  material.  A  4% latex content turned out to be effective  to keep swelling,  due to soaking  in water,  within a limit of 4,3%. Degree of compaction  has no significant  effect  of swell.  Degree of  compaction  and percentage  of  latex  content  has significant  effect  on bearing capacity.  Latex  may  be recommended   as an alternative  material for  stabilizing subgrade soil in forest  road construction.